Effects of a high protein, whey protein concentrate and spray-dried animal plasma on growth performance of weanling pigs - Grinstead, G.S.; Woodworth, J.C.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 35-d experiment was conducted to compare the effects of increasing spray-dried animal plasma and a high protein whey concentrate (73% CP) on starter pig performance. Spray-dried animal plasma and whey protein concentrate replaced dried skin1 milk on an equal lysine basis. Pigs fed increasing spray-dried animal plasma protein had increased ADG and ADFI from d 0 to 7 after weaning, but not for any other period in the study. Increasing whey protein concentrate had no effect on growth perforn1ance in relation to the pigs fed dried skim milk.
Keywords: Swine; Starter pigs; Spray-dried animal plasma; Whey protein concentrate